A naturally-occurring phenomenon of flower color change during flower development in Xanthoceras sorbifolium - Lu, Yanan; Wang, Hanhui; Liu, Zhi; Zhang, Tianxu; Li, Zongjian; Cao, Li; Wu, Siyao; Liu, Yueying; Yu, Song; Zhang, Qingzhu; Zheng, Zhimin (Frontiers in Plant Science, 2022)
Xanthoceras sorbifolium (yellowhorn) is originated in China and is a unique tree in northern China. Yellowhorn is very popular because of the gradual color change of its flower at different flower developmental stages. During flowering development, the color at the base of yellowhorn flower petals gradually changes from yellow to purple. The mechanism of this miraculous phenomenon is still unclear. Here we show that anthocyanin accumulation during flowering development is the main reason for this color change. RT-PCR results show that the expression level of a variety of anthocyanin biosynthesis genes changes in different flower developmental stages. Realtime results show that the expression changes of these anthocyanin biosynthesis genes are positively regulated by a cluster of R2R3-MYB transcription factor genes, XsMYB113s. Furthermore, the DNA methylation analysis showed that CHH methylation status on the transposon element near the XsMYB113-1 influence its transcript level during flowering development. Our results suggest that dynamic epigenetic regulation of the XsMYB113-1 leads to the accumulation of anthocyanins during yellowhorn flower color change. These findings reemphasize the role of epigenetic regulation in flower development and provide a foundation for further studies of epigenetic regulation in long-lived woody perennials.